PENCAPAIAN KOMPETENSI GURU SEKOLAH DASAR NEGERI MELALUI LESSON STUDYDI KOTA PAREPARE - Sitti Wardah Hanafie Das; Abdul Halik; Muhammad Nasir; Suredah Suredah (Universitas Muhammadiyah Semarang, 2017)
This study describes the teacher competence of state elementary school in Parepare, the forms of achievement, and the achievement of competencethrough lesson study. The objectives of the study are to understand the teachercompetence level, the models of teacher competence, and the strategy ofachieving teacher competence through the lesson study. The research method isqualitative, data source from education and culture office of Parepare,supervisor, and teacher. Data collection techniques through observation,interview, documentation, Focus Group Discussion (FGD), and triangulation.Data analysis techniques are reduction, analysis, verification, and conclusions.The result of the research shows that teacher of state elementary school inParepare have high level of competence with the Teacher Competence Exam(UKG) graduation in 2016 an average of 54% and that has been certified 90%of 881 teachers. The improvement of teacher competence form through trainingactivities by the education and culture office of Parepare, USAID LocalFacilitator (Fasda) of Parepare, Indonesian Teachers Union (PGRI) ofParepare, Teacher Working Group (KKG) and cluster program. Achievement ofteacher competence through lesson study conducted several stages, namelybrainstorming learning problems, solutions to the problem, learning planning,implementation of learning, and evaluation. Keywords: teacher, competence, quality, learning, lesson study